A Peer Assessment Approach for Learning from Public Health Emergencies. (November 2014) - Piltch-Loeb, Rachael N.; Nelson, Christopher D.; Kraemer, John D.; Savoia, Elena; Stoto, Michael A.
As an alternative to standard quality improvement approaches and to commonly used after action report/improvement plans, we developed and tested a peer assessment approach for learning from singular public health emergencies. In this approach, health departments engage peers to analyze critical incidents, with the goal of aiding organizational learning within and across public health emergency preparedness systems. We systematically reviewed the literature in this area, formed a practitioner advisory panel to help translate these methods into a protocol, applied it retrospectively to case studies, and later field-tested the protocol in two locations. These field tests and the views of the health professionals who participated in them suggest that this peer-assessment approach is feasible and leads to a more in-depth analysis than standard methods. Engaging people involved in operating emergency health systems capitalizes on their professional expertise and provides an opportunity to identify transferable best practices.